India in the shadows of empire a legal and political history, 1774-1950 - Mukherjee, Mithi (New Delhi : Oxford University Press, 2010)
Explaining the postcolonial Indian polity by presenting an alternative historical narrative of the British Empire in India and India's struggle for independence, this book follows two strands: firstly, the role of imperial judicial practices and institutions in the making of both the British Empire and the anti-colonial movement under the Congress, with the lawyer as political leader. Secondly, it shows that Gandhi's non-violent resistance movement was anchored not in western discourses of political and legislative freedom but rather in Indic traditions of renunciative freedom.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Constitutional history -- India; India -- History -- British occupation, 1765-1947.